Estudio fitoquímico y determinación de las flavanonas y alcaloides de naturaleza indolica en hojas de Perezia multiflora (H. et B.) Less "escorsonera" - Felix V., Luis (2000)
In the present investigation a phitochemical study of Prezia multiflora(H et B) lees Escorsonera was accomplished in order to determine the presence of secondary metabolites. A botanic study of this specie has been made to indicate its systematic location and morfhological description.A chemical and pharmacological review of the mayor components, as flavonoids and alcaloids; has also been performed. TLC and preparative chromatography were done, ending with the separation of two flavonoids. The identification of the flavonoid (flavonone type) as 7-O-RHAMNOGLUCOSIDE-3',5- DIHYDROXY -4'METOXYFLAVANONE, was done by UV spectroscopy. The other one probably would be: 3',5,7-TRIDIHYDROXY -4' -METOXYFLAVANONE. Two alcaloids were also identified and their probable structure would be: 1,4-(1,3-PIPERIDIL-DIENO)-2,5-0XO-6-HYDROXY-2H,3H-INDOL-ETENO and 1,4-(1,3-PIPERIDIL-DIENO)-2,5-0XO-6-0-GLUCOSYL-2H,3H-INDOLETENO.